WEBSITE INVENTORI DAN VISUALISASINYA - Ida Putu Ari Jayadinanta; I Ketut Gede Suhartana; Ida Ayu Gde Suwiprabayanti Putra (Jurusan Informatika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2024)
Information technology plays an important role in business with fast data processing and information retrieval. Access to information anytime and anywhere via the internet facilitates business. Web-based information systems meet information needs accurately. Efficient inventory system helps manage incoming, outgoing and stock items. Web-based inventory information system supports business processes. The HP inventory system and its visualizations are important in efficiently managing stock, product data, sales and shipping. The HP inventory system visualization provides a clear picture of inventory conditions, sales trends and business performance.